ANALISIS KOMPETENSI GURU FISIKA DALAM MENGIMPLEMENTASIKAN KTSP DI SMKN DI PROVINSI LAMPUNG - Sunaryo . (Jurnal Cakrawala Pendidikan, 2011)
Abstract: An Analysis of Physics Teachers’ Competencies in Implementing the School-Based Curriculum in State Vocational High Schools in Lampung Province. This study aims to investigate vocational high school physics teachers’ competencies in implementing the School-Based Curriculum. The sample consisted of 37 physics teacher from 27 state vocational high schools. Based on the data analysis, it can be concluded that physics teachers’ competencies in physics learning are good and they can satisfy the standards in accordance with their educational backgrounds. However, they need support in the form of laboratory facilities to improve learning outcomes. They are expected to understand the fundamental knowledge including logical, analytic, and systemic thinking, and meet the competence standards in the educational system. They also need information technology facilities to enhance their teaching skills. Keywords: teachers’ competencies, the School-Based Curriculum